Capacity strengthening of Post Graduates in climate smart agricutlure and climate information services - Diallo, Aboubacar; Doumbia, Salif; Dossou-Yovo, Elliott (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
Climate change poses persistent challenges to agricultural productivity, food security, and rural livelihoods in sub-Saharan Africa, particularly in rice-based systems where millions of smallholder farmers are vulnerable to climate variability. As part of its commitment to strengthening human capital and advancing climate-smart agriculture (CSA) and climate information services (CIS), the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project supported ten post-graduate researchers to conduct applied field research in Mali between January and June 2025. The research covered ten priority themes, including the integration of CSA technologies and CIS, gender-responsive innovations such as GEM parboiling, diversification with vegetables and tubers, water and nutrient management, rice-fish systems, innovation platforms, and climate suitability assessments. Findings demonstrated that combined adoption of CSA and CIS significantly improved rice yields, farm incomes, water productivity, food consumption scores, and adaptive capacity of smallholder farmers. Studies also highlighted key enablers for adoption, such as access to training, digital platforms for delivering geo-specific CIS, and inclusive innovation platforms that foster multi-stakeholder collaboration. The program not only generated critical evidence to inform policy and scaling strategies but also strengthened the technical, analytical, and leadership capacities of a new cadre of early-career scientists. The results underscore the importance of integrated approaches that combine technological, institutional, and social innovations to enhance resilience, productivity, and inclusiveness in rice-based systems under climate change. The report concludes with policy recommendations to support sustained scaling of CSA and CIS innovations while strengthening national research capacities in Mali and beyond.